Klasifikasi Jenis Perempuan Pekerja Rumahan di Kecamatan Blimbing - Uswatun Hasanah; Agus Hery; Idah Hadijah (Jurnal Inovasi Teknologi dan Edukasi Teknik, 2021)
The conduct of this study aims to classify and classify the types of work of women home-based workers according to what is done. This study used a purposive sampling method taken from women home-based workers in Blimbing District. The number of respondents consisted of 71 people. To find out the classification of home-based workers, researchers used a type of instrument in the form of open and closed questionnaires. The analysis of this research consists of four indicators, namely, respondent identity, job identification, family welfare, and social protection. Based on the results of the analysis, the recapitulation of the home-based workers respondents found that 21 people became self-employed workers, 20 people became intermediary workers, and 30 people became the putting-out system workers. The results of the data analysis found that 71.43 percent of the independent homeworkers show the criteria of being prosperous, 65 percent of the women intermediary homeworkers show the criteria are quite prosperous, 77 percent of the women homeworkers putting out the system show the criteria are quite prosperous. The results of data analysis on the social protection indicators show that 76.19 percent of the independent homeworkers show that the criteria are sufficiently protected, 45 percent of women intermediary homeworkers show the criteria are not protected, 63.33 percent of the women homeworkers putting out the system show the criteria are sufficiently protected. Diadakannya penelitian ini bertujuan untuk mengelompokkan serta mengklasifikasikan jenis pekerjaan perempuan pekerja rumahan sesuai dengan yang dikerjakan. Penelitian ini menggunakan metode purposive sampling yang diambil dari perempuan pekerja rumahan di Kecamatan Blimbing. Jumlah responden terdiri dari 71 orang. Untuk mengetahui klasifikasi pekerja rumahan, peneliti menggunakan jenis instrument berbentuk kuisioner terbuka dan tertutup. Analisis penelitian ini terdiri dari empat indikator yaitu, identitas responden, identifikasi pekerjaan, kesejahteraan keluarga, dan perlindungan sosial. Berdasarkan hasil analisis, rekapitulasi responden pekerja rumahan diketahui 21 orang menjadi pekerja mandiri, 20 orang menjadi pekerja perantara, dan 30 orang menjadi pekerja putting out system. Hasil analisis data pada indikator kesejahteraan keluarga diketahui 71.43 persen pekerja rumahan mandiri menunjukkan kriteria sejahtera, 65 persen perempuan pekerja rumahan perantara menunjukkan kriteria cukup sejahtera, 77 persen perempuan pekerja rumahan putting out system menunjukkan kriteria cukup sejahtera. Hasil analisis data pada indikator perlindungan sosial diketahui 76.19 persen pekerja rumahan mandiri menunjukkan kriteria cukup terlindungi, 45 persen perempuan pekerja rumahan perantara menunjukkan kriteria tidak terlindungi, 63.33 persen perempuan pekerja rumahan putting out system menunjukkan kriteria cukup terlindungi.